Assessment of Waste Generation Rate in Teaching Hospitals of Metropolitan City of Pakistan - Samita Arub; Sajid Rashid Ahmad; Sana Ashraf; Zahra Majid; Sadia Rahat; Rehan Iftikhar Paracha (Salehan Institute of Higher Education, 2020)
Hospital waste management is of vital significance owing to its contagious and hazardous nature as it can produce detrimental effects for both humans and the environment. This work aimed to examine types of waste with respect to waste generation rate in multiple teaching hospitals of metropolitan Lahore. A structured questionnaire survey, site visits, interviews and meetings were conducted in seventeen teaching hospitals. The results have shown that total hospitals average waste, infectious, non-infectious and waste generation rate in Lahore teaching hospitals were 38978 kg/day, 10789 kg/day, 28189 kg/day and 3.7 kg/bed/day, respectively. It is concluded that maximum waste generated in Mayo hospital, Jinnah hospital, Services hospital and Lahore general hospital was 16%, 12%, 12% and 10%, respectively, as per maximum patient’s visits. Positive liner correlation was between number of beds (P=0.917), number of accidents and emergency patients (P=0.75), infectious waste (P=0.998) and (P=1) with total waste. A straight line of linear regression was between (0.9966) infectious waste and (0.9995) general waste with average waste. Although, waste collection practices in these teaching hospitals were observed satisfactory but required training of doctors, nurses and hospital paramedical staff regarding infectious and general waste segregation. It is suggested that hospital staff, waste management and waste collection workers and respective waste management companies should be well trained and aware regarding infectious and non-infectious waste segregation, handling and disposing off procedures.